  • Matrices
• Algebra
• Geometry
• Funciones
• Trigonometry
• Coordinate geometry
• Combinatorics
 Suma y resta Producto por escalar Producto Inversa
 Monomials Polynomials Special products Equations Quadratic equations Radical expressions Systems of equations Sequences and series Inner product Exponential equations Matrices Determinants Inverse of a matrix Logarithmic equations Systems of 3 variables equations
 2-D Shapes Areas Pythagorean Theorem Distances
 Graphs Definition of slope Positive or negative slope Determine slope of a line Ecuación de una recta Equation of a line (from graph) Quadratic function Posición relativa de dos rectas Asymptotes Limits Distancias Continuity and discontinuities
 Sine Cosine Tangent Cosecant Secant Cotangent Trigonometric identities Law of cosines Law of sines
 Ecuación de una recta Posición relativa de dos rectas Distancias Angles in space Inner product

# Solve a quadratic equation by completing the square

With quadratic equations (ax2 + bx + c = 0), you can solve by completing the square.

Step 1: Make sure that the left side of the equation looks like x2 + bx.

Step 2: Add to both sides.

Step 3: Factor the left side as

Step 4: Take the square root and solve.

Solve by completing the square.

x2 - 2x - 3 = 0
Step 1: Make sure that the left side of the equation looks like x2 + bx.

To make the left side of the equation look like x2 + bx, add 3 to both sides.

 x2 - 2x - 3 = 0 x2 - 2x = 3

Step 2: Add to both sides.

Since b=-2,

 x2 - 2x = 3 x2 - 2x + 1 = 4

Step 3: Factor the left side as

In general, an expression of the form can be factored as

The expression x2 - 2x + 1 is of this form, with b=-2. So, it can be factored as (x-1)2.

Rewrite the equation with the left side factored.

(x-1)2 = 4

Step 4: Take the square root and solve.

 x - 1 = Take the square root x = Add 1 to both sides x = 1+2   or   x = 1-2         Split into + or - x=3 or x=-1 Simplify

Solve for by completing the square

t2-13t+36 = 0
t = or t =